1976
DOI: 10.1177/106591297602900309
|View full text |Cite
|
Sign up to set email alerts
|

Selected Determinants of Precinct Voting Decisions in School Budget Elections

Abstract: SOUND scientific method requires that any effort toward constructing a &dquo;grand~~ theory&dquo; of voting be preceded by additional research into relatively ne-S glected domains such as voting in local, nonpartisan elections. Research comparing individual or group correlates to voting in different types of elections' is sparse relative to the number of presidential election studies.' Both this research and the aggregate of research testing important theoretical assumptions in different local election setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results are consistent with those of other studies that showed little or no self-interest effects on government supported education when other factors were considered (Hall & Peile, 1976;Hamilton & Cohen, 1974;Smith, 1982). The results are also consistent with a growing body of research suggesting that citizens are not exclusively motivated by self-interest when they judge political objects and engage in political behavior (e.g., Kinder & Sears, 1981; Rasinski, 1984, Sears & Citrin, 1982Sears et al, 1979;Qler, 1986.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results are consistent with those of other studies that showed little or no self-interest effects on government supported education when other factors were considered (Hall & Peile, 1976;Hamilton & Cohen, 1974;Smith, 1982). The results are also consistent with a growing body of research suggesting that citizens are not exclusively motivated by self-interest when they judge political objects and engage in political behavior (e.g., Kinder & Sears, 1981; Rasinski, 1984, Sears & Citrin, 1982Sears et al, 1979;Qler, 1986.…”
Section: Discussionsupporting
confidence: 91%
“…Other major factors determining citizen support were citizens' deeply ingrained attitudes and schemata concerning government incompetence and waste, that is, their "symbolic attitudes." On the other hand, a number of studies of citizen support of public education have suggested that self-interest disappears as a factor when some non-self-interested factors are held constant (Hall & Peile, 1976;Hamilton & Cohen, 1974;Smith, 1982). In fact, research suggests that the citizen's sense of public responsibility may completely overcome his or her own self-interest when making decisions about public services and the funding of such services (Cook, 1979;Smith, 1982;Wilson & Banfield, 1964).…”
Section: Northwestem Univemiymentioning
confidence: 99%